2009
DOI: 10.3844/ajbbsp.2009.162.169
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drought Stress and Methanol on Yield and Yield Components of Soybean Max (L 17)

Abstract: Problem statement:In order to evaluate drought stress and methanol on yield and yield components of soybean in field experiments with factorial experiment inform of a randomized complete block design with three replication in field faculty of agricultural of Islamic Azad University Karaj, at 2008. First factor were sprayed aqueous solutions 0 (control), 7, 14.21, 28 and 35% (v/v) methanol by 3 times during growth season of soybean with 12 days intervals on shoot of soybean. Second factor were drought stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
1
16
1
1
Order By: Relevance
“…4). In condition of drought stress in soybean, Mirakhori et al (2009) observed a decrease in the number of branches per plant, as well as plant height, number of pod per plant and soybean grain yield.…”
Section: Number Of Branches Per Plant and 1000-grain Weight Of Soybeanmentioning
confidence: 95%
“…4). In condition of drought stress in soybean, Mirakhori et al (2009) observed a decrease in the number of branches per plant, as well as plant height, number of pod per plant and soybean grain yield.…”
Section: Number Of Branches Per Plant and 1000-grain Weight Of Soybeanmentioning
confidence: 95%
“…Mirakhori et al [16] studied drought stress and methanol on yield and yield components of soybean in field experiments with factorial experiment in the form of a randomized complete block design with three replication in field. First factor were sprayed aqueous solutions 0 (control), 7, 14,21, 28 and 35% (v/v) methanol by 3 times during growth season of soybean with 12 days intervals on shoot of soybean.…”
Section: Doan and Maurelmentioning
confidence: 99%
“…Water also have been a limited resource in agriculture and its must be use efficiently. Water also one of the most important limiting factors in plant growth other than Nitrogen (Sajedi et al, 2009;Mirakhori et al, 2009;Schindler et al, 2007;Xu and Yu, 2006;Fan and Zhang, 2000). In plant relations, determination of the water requirement of plant is important for agriculture in dry regions (Gholizadeh et al, 2010;Fuller and Harhay, 2010).…”
Section: Introductionmentioning
confidence: 99%